Understanding Introductory Accounting: Locus, Emotion, Learning, and Interest Nexus: Menggali Nexus Locus of Control, Emotional Intelligence, Proses Pembelajaran, dan Minat Belajar: Studi Kuantitatif tentang Pemahaman Mata Kuliah Akuntansi Dasar. - Dwi Auliyah; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2022)
This study investigates the influence of locus of control, emotional intelligence, and the learning process on the understanding of introductory accounting courses, while also exploring the moderating role of interest in learning. A nonprobability purposive sampling method was employed to gather responses from 131 accounting students enrolled in the fourth semester of 2019 at Muhammadiyah University of Sidoarjo. The collected data was analyzed using a data quality test and Moderated Analysis Regression (MRA) with SPSS version 18 for Windows. The findings reveal that locus of control, emotional intelligence, and the learning process positively and significantly affect the understanding of introductory accounting courses. However, interest in learning was found to have no moderating effect on the influence of locus of control or emotional intelligence, while it did moderate the influence of the learning process. These findings contribute to the understanding of the factors impacting the comprehension of introductory accounting courses, emphasizing the importance of locus of control, emotional intelligence, and the learning process, as well as the role of interest in learning in the educational context. Highlights: The study examines the impact of locus of control, emotional intelligence, and the learning process on understanding introductory accounting courses. It investigates whether interest in learning moderates the relationship between these factors and comprehension of the subject. The findings highlight the significance of locus of control, emotional intelligence, and the learning process in enhancing the understanding of introductory accounting courses, emphasizing the role of interest in learning as a moderator. Keywords: Locus of Control, Emotional Intelligence, Learning Process, Interest in Learning, Introductory Accounting Courses.